Media development board game to increase student motivation in studying regional culture - Khusnul Khotimah; Neni Wahyuningtyas (Jurnal Inovasi Teknologi Pendidikan, 2023)
Media development as an effort to introduce regional culture is considered essential to do. Technological developments make students' motivation to study culture begin to fade and shift with the emergence of Western civilization. This is motivated by the need for more interesting local culture introduction media for students and regional, cultural, and educational content in online or offline media. Therefore, learning media is needed to introduce regional culture. The objectives of this development research are: (1) Producing culture game education media board game products; (2) Testing and knowing the feasibility of culture game education media board game products; and (3) Knowing the effectiveness of culture game education board game media products in increasing learning motivation on material Sub Theme 2: "The Beauty of My Country's Cultural Diversity" for grade IV Elementary School. The development model used is ADDIE. The results of this development research are: (1) Learning media products, board game culture, and game education; and (2) Based on the validation that has been carried out on material experts and learning media experts, it is stated that the culture game education board game is suitable for use in the learning process and can be implemented for students with a percentage of the validity test of material experts, namely 89% and a percentage of the validity test of learning media experts, namely 98%. The results of the practicality test using the culture game education board game by the teacher obtained a score of 91%, while the trial results related to the percentage of students' motivation to learn culture through this media was 86%. The conclusion is based on the development done; the culture game education board game is declared appropriate when used as a medium to introduce regional culture.